2017
DOI: 10.1002/cne.24257
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of nNOS neurons in the postnatal and adult female mouse hypothalamus

Abstract: Neurons expressing nitric oxide (NO) synthase (nNOS) and thus capable of synthesizing NO play major roles in many aspects of brain function. While the heterogeneity of nNOS-expressing neurons has been studied in various brain regions, their phenotype in the hypothalamus remains largely unknown. Here we examined the distribution of cells expressing nNOS in the postnatal and adult female mouse hypothalamus using immunohistochemistry. In both adults and neonates, nNOS was largely restricted to regions of the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 71 publications
3
43
0
Order By: Relevance
“…Furthermore, progestin receptors are also present in the lateral part of the VMH and its expression is highly dependent on estrogens 49 52 . Finally, a recent study 53 showed that close to 100% of neurons expressing estradiol receptors in the VMHvl are actually nNOS-expressing neurons. Taken together, these findings reveal that kisspeptin neurons communicate with nNOS neurons in the VMHvl, a central hub driving female sexual behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, progestin receptors are also present in the lateral part of the VMH and its expression is highly dependent on estrogens 49 52 . Finally, a recent study 53 showed that close to 100% of neurons expressing estradiol receptors in the VMHvl are actually nNOS-expressing neurons. Taken together, these findings reveal that kisspeptin neurons communicate with nNOS neurons in the VMHvl, a central hub driving female sexual behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, progestin receptors are also present in the lateral part of the VMH and its expression is highly dependent on estrogens [49][50][51][52] . Finally, a recent study 53 showed that close to 100% of neurons expressing estradiol receptors in the VMHvl are actually nNOS-expressing neurons. Taken together, these findings reveal that kisspeptin neurons communicate with nNOS neurons in the VMHvl, a central hub driving female sexual behavior.…”
Section: Discussionmentioning
confidence: 96%
“…It is interesting to note that close to 100% of neurons expressing estradiol receptors in the VMHvl are actually nNOS expressing neurons. 55 However, it cannot be ruled out that other nNOS populations are also involved, for instance, in the OVLT, where nNOS neurons are part of a neural circuit regulating ovarian cyclicity and ovulation. 56 It is interesting to note that mating stimulation induced an activation of nNOS neurons in the OVLT as measured by the number of phosphorylated nNOS (pnNOS) neurons (►Fig.…”
Section: Alternative Pathway Involving No-synthesizing Neurons In Lormentioning
confidence: 99%